Public Health Consequences of E-Cigarettes - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Millions of Americans use e-cigarettes. Despite their popularity, little is known about their health effects. Some suggest that e-cigarettes likely confer lower risk compared to combustible tobacco cigarettes, because they do not expose users to toxicants produced through combustion. Proponents of e-cigarette use also tout the potential benefits of e-cigarettes as devices that could help combustible tobacco cigarette smokers to quit and thereby reduce tobacco-related health risks. Others are concerned about the exposure to potentially toxic substances contained in e-cigarette emissions, especially in individuals who have never used tobacco products such as youth and young adults. Given their relatively recent introduction, there has been little time for a scientific body of evidence to develop on the health effects of e-cigarettes. Public Health Consequences of E-Cigarettes reviews and critically assesses the state of the emerging evidence about e-cigarettes and health. This report makes recommendations for the improvement of this research and highlights gaps that are a priority for future research.
Keywords: Health and Medicine

Global Health and the Future Role of the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
While much progress has been made on achieving the Millenium Development Goals over the last decade, the number and complexity of global health challenges has persisted. Growing forces for globalization have increased the interconnectedness of the world and our interdependency on other countries, economies, and cultures. Monumental growth in international travel and trade have brought improved access to goods and services for many, but also carry ongoing and ever-present threats of zoonotic spillover and infectious disease outbreaks that threaten all. Global Health and the Future Role of the United States identifies global health priorities in light of current and emerging world threats. This report assesses the current global health landscape and how challenges, actions, and players have evolved over the last decade across a wide range of issues, and provides recommendations on how to increase responsiveness, coordination, and efficiency – both within the U.S. government and across the global health field.
Keywords: Health and Medicine

Promoting Cardiovascular Health in the Developing World: A Critical Challenge to Achieve Global Health - Institute of Medicine (The National Academies Press, 2010)
Cardiovascular disease (CVD), once thought to be confined primarily to industrialized nations, has emerged as a major health threat in developing countries. Cardiovascular disease now accounts for nearly 30 percent of deaths in low and middle income countries each year, and is accompanied by significant economic repercussions. Yet most governments, global health institutions, and development agencies have largely overlooked CVD as they have invested in health in developing countries. Recognizing the gap between the compelling evidence of the global CVD burden and the investment needed to prevent and control CVD, the National Heart, Lung, and Blood Institute (NHLBI) turned to the IOM for advice on how to catalyze change. In this report, the IOM recommends that the NHLBI, development agencies, nongovernmental organizations, and governments work toward two essential goals: creating environments that promote heart healthy lifestyle choices and help reduce the risk of chronic diseases, and building public health infrastructure and health systems with the capacity to implement programs that will effectively detect and reduce risk and manage CVD. To meet these goals, the IOM recommends several steps, including improving cooperation and collaboration; implementing effective and feasible strategies; and informing efforts through research and health surveillance. Without better efforts to promote cardiovascular health, global health as a whole will be undermined.
Keywords: Health and Medicine

Exploring Strategies to Improve Cardiac Arrest Survival: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Cardiac arrest often strikes seemingly healthy individuals without warning and without regard to age, gender, race, or health status. Representing the third leading cause of death in the United States, cardiac arrest is defined as "a severe malfunction or cessation of the electrical and mechanical activity of the heart ... [which] results in almost instantaneous loss of consciousness and collapse". Although the exact number of cardiac arrests is unknown, conservative estimates suggest that approximately 600,000 individuals experience a cardiac arrest in the United States each year. In June 2015, the Institute of Medicine (IOM) released its consensus report Strategies to Improve Cardiac Arrest Survival: A Time to Act, which evaluated the factors affecting resuscitation research and outcomes in the United States. Following the release of this report, the National Academies of Sciences, Engineering, and Medicine was asked to hold a workshop to explore the barriers and opportunities for advancing the IOM recommendations. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

A Nationwide Framework for Surveillance of Cardiovascular and Chronic Lung Diseases - Institute of Medicine (The National Academies Press, 2011)
Chronic diseases are common and costly, yet they are also among the most preventable health problems. Comprehensive and accurate disease surveillance systems are needed to implement successful efforts which will reduce the burden of chronic diseases on the U.S. population. A number of sources of surveillance data—including population surveys, cohort studies, disease registries, administrative health data, and vital statistics—contribute critical information about chronic disease. But no central surveillance system provides the information needed to analyze how chronic disease impacts the U.S. population, to identify public health priorities, or to track the progress of preventive efforts. A Nationwide Framework for Surveillance of Cardiovascular and Chronic Lung Diseases outlines a conceptual framework for building a national chronic disease surveillance system focused primarily on cardiovascular and chronic lung diseases. This system should be capable of providing data on disparities in incidence and prevalence of the diseases by race, ethnicity, socioeconomic status, and geographic region, along with data on disease risk factors, clinical care delivery, and functional health outcomes. This coordinated surveillance system is needed to integrate and expand existing information across the multiple levels of decision making in order to generate actionable, timely knowledge for a range of stakeholders at the local, state or regional, and national levels. The recommendations presented in A Nationwide Framework for Surveillance of Cardiovascular and Chronic Lung Diseases focus on data collection, resource allocation, monitoring activities, and implementation. The report also recommends that systems evolve along with new knowledge about emerging risk factors, advancing technologies, and new understanding of the basis for disease. This report will inform decision-making among federal health agencies, especially the Department of Health and Human Services; public health and clinical practitioners; non-governmental organizations; and policy makers, among others.
Keywords: Health and Medicine

Advancing Obesity Solutions Through Investments in the Built Environment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The built environment—the physical world made up of the homes, buildings, streets, and infrastructure within which people live, work, and play—underwent changes during the 20th and 21st centuries that contributed to a sharp decline in physical activity and affected access to healthy foods. Those developments contributed in turn to the weight gain observed among Americans in recent decades. Many believe, therefore, that policies and practices that affect the built environment could affect obesity rates in the United States and improve the health of Americans. The National Academies of Sciences, Engineering, and Medicine convened a workshop in September 2017 to improve understanding of the roles played by the built environment in the prevention and treatment of obesity and to identify promising strategies in multiple sectors that can be scaled up to create more healthful and equitable environments. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Strategies to Improve Cardiac Arrest Survival: A Time to Act - Institute of Medicine (The National Academies Press, 2015)
Cardiac arrest can strike a seemingly healthy individual of any age, race, ethnicity, or gender at any time in any location, often without warning. Cardiac arrest is the third leading cause of death in the United States, following cancer and heart disease. Four out of five cardiac arrests occur in the home, and more than 90 percent of individuals with cardiac arrest die before reaching the hospital. First and foremost, cardiac arrest treatment is a community issue - local resources and personnel must provide appropriate, high-quality care to save the life of a community member. Time between onset of arrest and provision of care is fundamental, and shortening this time is one of the best ways to reduce the risk of death and disability from cardiac arrest. Specific actions can be implemented now to decrease this time, and recent advances in science could lead to new discoveries in the causes of, and treatments for, cardiac arrest. However, specific barriers must first be addressed. Strategies to Improve Cardiac Arrest Survival examines the complete system of response to cardiac arrest in the United States and identifies opportunities within existing and new treatments, strategies, and research that promise to improve the survival and recovery of patients. The recommendations of Strategies to Improve Cardiac Arrest Survival provide high-priority actions to advance the field as a whole. This report will help citizens, government agencies, and private industry to improve health outcomes from sudden cardiac arrest across the United States.
Keywords: Health and Medicine

Secondhand Smoke Exposure and Cardiovascular Effects: Making Sense of the Evidence - Institute of Medicine (The National Academies Press, 2010)
Data suggest that exposure to secondhand smoke can result in heart disease in nonsmoking adults. Recently, progress has been made in reducing involuntary exposure to secondhand smoke through legislation banning smoking in workplaces, restaurants, and other public places. The effect of legislation to ban smoking and its effects on the cardiovascular health of nonsmoking adults, however, remains a question. Secondhand Smoke Exposure and Cardiovascular Effects reviews available scientific literature to assess the relationship between secondhand smoke exposure and acute coronary events. The authors, experts in secondhand smoke exposure and toxicology, clinical cardiology, epidemiology, and statistics, find that there is about a 25 to 30 percent increase in the risk of coronary heart disease from exposure to secondhand smoke. Their findings agree with the 2006 Surgeon General's Report conclusion that there are increased risks of coronary heart disease morbidity and mortality among men and women exposed to secondhand smoke. However, the authors note that the evidence for determining the magnitude of the relationship between chronic secondhand smoke exposure and coronary heart disease is not very strong. Public health professionals will rely upon Secondhand Smoke Exposure and Cardiovascular Effects for its survey of critical epidemiological studies on the effects of smoking bans and evidence of links between secondhand smoke exposure and cardiovascular events, as well as its findings and recommendations.
Keywords: Health and Medicine

Driving Action and Progress on Obesity Prevention and Treatment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
After decades of increases in the obesity rate among U.S. adults and children, the rate recently has dropped among some populations, particularly young children. What are the factors responsible for these changes? How can promising trends be accelerated? What else needs to be known to end the epidemic of obesity in the United States? To examine these and other pressing questions, the Roundtable on Obesity Solutions, of the National Academies of Sciences, Engineering, and Medicine, held a workshop in September 2016. The workshop brought together leaders from business, early care and education, government, health care, and philanthropy to discuss the most promising approaches for the future of obesity prevention and treatment. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Assessing Prevalence and Trends in Obesity: Navigating the Evidence - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Obesity has come to the forefront of the American public health agenda. The increased attention has led to a growing interest in quantifying obesity prevalence and determining how the prevalence has changed over time. Estimates of obesity prevalence and trends are fundamental to understanding and describing the scope of issue. Policy makers, program planners, and other stakeholders at the national, state, and local levels are among those who search for estimates relevant to their population(s) of interest to inform their decision-making. The differences in the collection, analysis, and interpretation of data have given rise to a body of evidence that is inconsistent and has created barriers to interpreting and applying published reports. As such, there is a need to provide guidance to those who seek to better understand and use estimates of obesity prevalence and trends. Assessing Prevalence and Trends in Obesity examines the approaches to data collection, analysis, and interpretation that have been used in recent reports on obesity prevalence and trends at the national, state, and local level, particularly among U.S. children, adolescents, and young adults. This report offers a framework for assessing studies on trends in obesity, principally among children and young adults, for policy making and program planning purposes, and recommends ways decision makers and others can move forward in assessing and interpreting reports on obesity trends.
Keywords: Food and Nutrition

The Challenge of Treating Obesity and Overweight: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Roundtable on Obesity Solutions of the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, on April 6, 2017, titled The Challenge of Treating Obesity and Overweight: A Workshop. The discussions covered treatments for obesity, overweight, and severe obesity in adults and children; emerging treatment opportunities; the development of a workforce for obesity treatments; payment and policy considerations; and promising paths to move forward. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition